The correlation of oxidative stress with physical performance in cyclist - Murawska-Cialowicz, E.; Jethon, Z.; Samolyk, A.; Wierzbicka-Damska, I.; Szafraniec, R. (8th International Sports Science Conference, Vilnius, 25-26 February 2005, 2005)
The aim of investigation performed was the difference of oxidative stress level in correlation with physical work performance and starting periods. The results show statistically significant changes of physiological parameters indicating an elevation of physical performance. The differences between pre-starting and starting periods were greater in the group P. Comparison of the changes in respect to the investigated groups indicate that the physiological cost of physical test was lower in the group N (Polish National Team). The oxidative stress level, measured by the concentration of MDA and 4HDA, was higher during the pre-starting period and more distinct in the group P (cyclists attending a secondary sport school in Wroclaw). During the starting period in both groups the level of oxidative stress was similar, statistically insignificant. The results received show that the oxidative stress level is variable during the training related to the phase of training cycle. An elevation of physical performance diminishes the oxidative stress effects, while in the investigated sport discipline the decrease was in little amount correlated with the level of physical performance.